مقارنة الدوكسي سيكلين الفموي مع الأزيترومايسين الفموي في علاج العدّ الشائع - بدور, رولا (Latakia University Journal -Medical Sciences Series, 2019)
this study has included 78 Patients having acne vulgaris on face. Patients were randomily divided into two groups, Patients in first group were given azithromycin 500 mg daily before meal for 3 consecutive days monthly for 3 months while Patients in second group were given doxycycline 100 mg daily after meals for 3 months. Patients were followed up after taking treatment for 1 month and 3 months to see the response and tolerance of each drug. Result: there was no significant difference between two groups regarding the amount of decrease in acne severity index across the study but azithromycin was more tolerable than doxycycline. تمّت الدراسة على 78 مريضاً لديهم عُدّ شائع في الوجه. تم تقسيم المرضى إلى مجموعتين، تلقّت المجموعة الاولى الأزيترومايسين النبضي بجرعة 500 ملغ يومياً على الريق لـ 3 أيام متتالية بفواصل شهرية ولمدة ثلاثة أشهر، فيما تلقّت المجموعة الثانية دوكسي سيكلين بجرعة 100 ملغ يومياً بعد الطعام لمدة 3 أشهر. تم متابعة المرضى بعد تلقي العلاج وذلك بعد شهر وبعد ثلاثة أشهر لتسجيل الاستجابة وكذلك التحمّل لكلا العقارين. بالنتيجة، كانت الاستجابة لكلا الدوائين متقاربة فيما يتعلق بتحسُّن مشعر شدة العدّ مع وجود فارق هام إحصائياً(P=0.186)في حين كان تحمّل الأزيترومايسين افضل من تحمل الدوكسي سيكلين.